DEVELOPMENT OF ELECTRONIC LEARNING MEDIA PACAL RESERVIOR MATERIAL FOR PHASE F CLASS XI SMAN 1 BAURENO - Sholikah, Dini Nisa Atus; Lutfi, Ismail (Universitas Negeri Malang, 2024)
Abstract:This study aims to develop effective and interactive learning materials for Pacal Reservoir content within Phase F, Class XI at SMAN 1 Baureno, employing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. Emphasizing the creation of interactive learning resources, the research endeavors to enhance students' comprehension of the technical and environmental aspects associated with the Pacal Reservoir. Methodologically, the research employs learning needs analysis, media design, development based on predetermined designs, implementation within the classroom setting, and evaluation of the efficacy of the developed learning materials. Notably, the active involvement of students and teachers in the development process plays a pivotal role in ensuring that the produced learning materials address identified needs and effectively enhance student engagement and comprehension of the Pacal Reservoir content. It is anticipated that the findings of this study will contribute to the enhancement of the quality of learning materials pertaining to the Pacal Reservoir at SMAN 1 Baureno, while also serving as a valuable reference for the development of similar learning resources across related fields of study.